2020
DOI: 10.1037/xge0000732
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of free recall: The role of rehearsal efficiency in word frequency and bilingual language proficiency effects.

Abstract: Under a recall model in which presentations and rehearsals are treated as equivalent encoding events, we investigated whether rehearsal efficiency differences explain the effects of word frequency and bilingual proficiency on the temporal dynamics of rehearsal and free recall. Experiments 1 and 3 were conducted with monolingual English speakers, and Experiments 2 and 4 were conducted with Spanish-English bilinguals with matched age, education, and socioeconomic status. In Experiments 1 and 2, lower word freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
(221 reference statements)
0
3
0
Order By: Relevance
“…Detecting free recall performance differences across languages may require having participants memorize a larger number of lists. In previous studies with the same participant population, we found no reliable difference between L1 and L2 free recall accuracy when there was only one list per language (Francis & Baca, 2014), but there was a clear advantage for L1 over L2 recall when participants memorized sixteen lists in each language (Francis et al, 2018).…”
Section: Free Recall Accuracymentioning
confidence: 48%
See 2 more Smart Citations
“…Detecting free recall performance differences across languages may require having participants memorize a larger number of lists. In previous studies with the same participant population, we found no reliable difference between L1 and L2 free recall accuracy when there was only one list per language (Francis & Baca, 2014), but there was a clear advantage for L1 over L2 recall when participants memorized sixteen lists in each language (Francis et al, 2018).…”
Section: Free Recall Accuracymentioning
confidence: 48%
“…In one study, bilingual younger and older adults performed worse than monolingual adults (matched on age and non-verbal intelligence scores) in free recall of English word lists in which all words came from the same semantic category (Fernandes, Craik, Bialystok, & Kreuger, 2007). In the other, highly proficient bilingual adults performed worse in L2 but not in L1 relative to monolinguals who were matched on age, non-verbal cognitive ability, and socio-economic status in free recall of word lists with no categorical structure (Francis, Liaño, & Taylor, 2018).…”
Section: Recall and Semantic Clustering In Bilingual Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Mizrahi et al [57] predicted that bilinguals would be disadvantaged in free recall, but advantaged in recognition in the nondominant language. In this vein, previous studies confirmed that bilinguals recalled fewer items, exhibited worse memory for item order, and weaker primacy effects in the nondominant than the dominant language [58][59][60]. In addition, two more studies reported better recognition memory for words in bilinguals' nondominant compared to their dominant language [61,62].…”
Section: Present Studiesmentioning
confidence: 76%